Evaluation of research ethics committees: criteria for the ethical quality of the review process - Scherzinger, Gregor; Bobbert, Monika (Accountability in research, 2017)
Repeatedly, adequacy, performance and quality of Ethics Committees that oversee medical research trials are being discussed. Although they play a crucial role in reviewing medical research and protecting human subjects, it is far from clear to what degree they fulfill the task they have been assigned to. This eventuates in the call for an evaluation of their activity and, in some places, led to the establishment of accreditation schemes. At the same time, IRBs have become subject of detailed legislation in the process of the ongoing global juridification of medical research. Unsurprisingly, there is a tendency to understand the evaluation of RECs as a question of controlling their legal compliance. This paper discusses the need for a quality evaluation of IRBs from an ethical point of view and, by systematically reviewing the major ethical guidelines for IRBs, proposes a system of criteria that should orientate any evaluation of IRBs.
Gesehen am 12.05.2021